2012
DOI: 10.1515/astro-2017-0406
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Sunspot with a Dark Patch in the Coronal Emission

Abstract: On the base of the 17 GHz radio maps of the Sun taken with the Nobeyama Radio Heliograph we estimate plasma parameters in the specific region of the sunspot atmosphere in the active region AR 11312. This region of the sunspot atmosphere is characterized by the depletion in coronal emission (soft X-ray and EUV lines) and the reduced absorption in the a chromospheric line (He I 1.083 μm). In the ordinary normal mode of 17 GHz emission the corresponding dark patch has the largest visibility near the central solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The quiet-Sun level is defined to be 10 4 K in right and left circular polarization as well. Bezrukov et al (2011) andShibasaki (2012) converted I and V maps into R = I + V and L = I − V maps in their study of the depressed 17 GHz emission. In the NoRH database I and V maps were routinely produced with dissimilar CLEAN parameters in the image reconstruction process.…”
Section: Observationsmentioning
confidence: 99%
“…The quiet-Sun level is defined to be 10 4 K in right and left circular polarization as well. Bezrukov et al (2011) andShibasaki (2012) converted I and V maps into R = I + V and L = I − V maps in their study of the depressed 17 GHz emission. In the NoRH database I and V maps were routinely produced with dissimilar CLEAN parameters in the image reconstruction process.…”
Section: Observationsmentioning
confidence: 99%
“…In other cases, it was suggested that a general low temperature plasma volume overlies some parts of the sunspot. In particular, several authors (Alissandrakis and Kundu 1982;Strong, Alissandrakis, and Kundu, 1984;White, Kundu, and Gopalswamy, 1991;Zlotnik, Kundu, and White, 1996;Zlotnik, White, and Kundu, 1998;Bezrukov et al, 2011;Bezrukov, Ryabov, and Shibasaki, 2012) invoked low temperature plasma above the center of the sunspot and at the relevant gyroresonance levels to explain the observed reduction in emission more pronounced than expected due to the small angle between the magnetic field and the line of sight there. Brosius and White (2004) additionally directly observed enhanced transition region EUV emission ("sunspot plume") at the location of reduced microwave emission in coordinated EUV observations with SOHO/CDS.…”
Section: Introductionmentioning
confidence: 99%